2020
DOI: 10.1016/j.molp.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The IBI1 Receptor of β-Aminobutyric Acid Interacts with VOZ Transcription Factors to Regulate Abscisic Acid Signaling and Callose-Associated Defense

Abstract: External and internal signals can prime the plant immune system for a faster and/or stronger response to pathogen attack. β-aminobutyric acid (BABA) is an endogenous stress metabolite that induces broad-spectrum disease resistance in plants. BABA perception in Arabidopsis is mediated by the aspartyl tRNA synthetase IBI1, which activates priming of multiple immune responses, including callose-associated cell wall defenses that are under control by abscisic acid (ABA). However, the immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 80 publications
1
48
0
Order By: Relevance
“…2A-B). Since RBH-IR against Hpa in Arabidopsis is associated with augmented effectiveness of callose-rich papillae (Buswell et al, 2018), we quantified the effectiveness callose-mediated cell wall defence at 3 dpi, as detailed previously (Schwarzenbacher et al, 2020). All original iri lines consistently lacked RBH-IR and concomitantly failed to augment callose-mediated defence upon RBH treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A-B). Since RBH-IR against Hpa in Arabidopsis is associated with augmented effectiveness of callose-rich papillae (Buswell et al, 2018), we quantified the effectiveness callose-mediated cell wall defence at 3 dpi, as detailed previously (Schwarzenbacher et al, 2020). All original iri lines consistently lacked RBH-IR and concomitantly failed to augment callose-mediated defence upon RBH treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…VOZ1 and VOZ2 are transcription factors that belong to the NAC transcription factor family, and were reported as involved in the control of flowering time (Celesnik et al, 2013; Yasui and Kohchi, 2014), either through the binding of PhyB (Yasui et al, 2012), Flowering Locus C (Mimida et al, 2011) or Constans (Koguchi et al, 2017; Kumar et al, 2018). VOZ proteins were also related to biotic and abiotic stress responses (Nakai et al, 2013; Song et al, 2018; Schwarzenbacher et al, 2020; Wang et al, 2021). VOZ1 and VOZ2 were proved to be functionally redundant, as single mutants for each gene showed normal phenotypes, but voz1voz2 double mutants displayed phenotypic defects (Yasui et al, 2012; Celesnik et al, 2013; Nakai et al, 2013; Kumar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that BABA induces a variety of defense mechanisms, including production of phenolics, ROS, PR proteins, callose, lignin and more, depending on the host–pathogen system [ 21 , 25 , 34 , 35 , 36 , 37 ]. In a recent study, Schwarzenbacher et al [ 38 ] showed that BABA interacts with VOZ transcription factors to regulate abscisic acid signaling and callose-associated defense against downy mildew in Arabidopsis. The reactions of apple tissue to BABA warrants a special study.…”
Section: Discussionmentioning
confidence: 99%